Safety Literacy and Societal Well-Being: A Case Study of Ibadan North Local Government Area, Ibadan, Oyo State Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research examines safety literacy in the particular setting of the Ibadan North Local Government Area in Nigeria. It does so by providing a thorough analysis of current levels, contextual and cultural influences, the relationship to societal well-being, and the identification of obstacles to improvement. Utilizing a descriptive survey design approach and a stratified random sampling, the study measures safety literacy by means of quantitative evaluations of understanding and awareness. It examines how context and culture affect people's understanding of safety, highlighting the importance of culturally appropriate safety instruction. The study reveals a high level of safety literacy, cultural and contextual factors emerge as crucial determinants, shaping safety practices based on local beliefs, practices, and norms. The observed correlation between safety literacy and societal well-being underscores the profound influence of informed safety practices on community health, economic stability, social cohesion, and collective responsibility. Nonetheless, the study points out several obstacles that stand in the way of enhancing safety literacy, such as restricted information availability, difficulties with language, and cultural resistance. These obstacles highlight the need for focused interventions to address particular issues impeding the community's efforts to improve safety literacy.